Miniaturised structure design, modelling and simulation process for active engine mounts. (8th February 2021) - Wang, Pu; Fan, Rang-Lin; Xing, Zeng-Yao; Zhang, Wei-Cun; Wu, Quan-Fa
Active engine mounts (AEMs) provide an effective solution to further improve the dynamic comfort of passenger cars in noise and vibration and tend to be miniaturised to reduce the space occupation. This paper focuses on the miniaturised structure design process and the corresponding modelling and simulation. Two types of electromagnetic AEMs with oscillating coil actuator or solenoid actuator were compared in space occupation, sealing performance, cost, static load capacity and dynamic performance, and their advantages and disadvantages were summarised, then the optimal design of the miniaturised structure was carried out using the finite element model (FEM) and lumped parameter model (LPM) and simulations. The final design of the miniaturised AEM had small dimensions and similar performance to those ordinary AEMs. The miniaturised design and simulation process shown in this article can improve the space utilisation of AEM while ensuring no performance degradation.